Collaborative Agents - Research and Development International Workshops, CARE@AI09 2009 / CARE@IAT10 2010, Melbourne Australia, December 1, 2009 and Toronto Canada, August 31, 2010, Revised Selected Papers - Guttmann, Christian; Dignum, Frank; Georgeff, Michael; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the first two international workshops on computational models of collaboration in distributed systems: CARE 2009, held as satellite event of the 22nd Australasian Joint Conference on Artificial Intelligence AI09 in Melbourne, Australia, in December 2009 and CARE 2010, held in conjunction with the International Conference on Intelligent Agent Technology (IAT) in Toronto, Canada, in August 2010. The 12 revised full papers presented together with 2 invited lectures were carefully selected from a total of 45 submissions to both events. The workshops' thematic focus is on collaborative and autonomous agents that plan, negotiate, coordinate, and act under conditions of incomplete information, uncertainty, and bounded rationality.
Electronic reproduction.
Keywords: Computer science; Computer Communication Networks; Data mining; Information systems; Artificial intelligence; Intelligent agents (Computer software) -- Congresses; Distributed artificial intelligence -- Congresses; Electronic books